Finite element analysis of Graphite-Thermoplastic composite of bipolar plate in Proton Exchange Membrane Fuel Cell (PEMFC) using solidworks® software - Beh, Pei Xin (2019)
The purpose of this study was to simulate the mechanical performance of the bipolar plate (BPP) in proton exchange membrane fuel cell (PEMFC). PEMFC increased the productivity of automotive by freeing the automobile from carnot cycle subsequently increased the working efficiency. Besides, automobile, which applied PEMFC, emitted low volume of greenhouse gas since consuming less petroleum. These synergic effects promoted the air quality thus protected the health of living creatures. BPP occupied around 80 % of weight and 30 % of PEMFC overall cost. Consideration was given to BPP to reduce the weight of automobile to ensure fuel was used efficiently to move the load rather than weight of automobiles. Material of BPP should be lightweight with high strength to withstand high clamping pressure ensuring smooth operation of PEMFC. Hence, the research would focus on PPS-graphite thermoplastic composite BPP. Model of BPP was sketched using SolidWorks® software adhered to the experimental-scale parallel flow field design and compared with reference serpentine flow field BPP by applying 280 N nodal force. The result showed that parallel flow field BPP was better than serpentine flow field BPP with even stress distribution and PPS-graphite BPP showed the least stress intensity. Four different pressure, which was 250 kPa, 500 kPa, 750 kPa, 1 000 kPa were applied to simulate high clamping pressure environment and PPS-graphite BPP showed the least displacement among the three different material of BPP. Thermal stress and displacement was simulated with high temperature and expansion restrained environment. The analysis of data revealed that PPS-graphite BPP was subjected to high thermal stress and displacement due to high thermal expansion coefficient. Based on the overall analysis of data, PPS-graphite BPP performed ideally when subjected to static clamping pressure but performance degraded due to high thermal stress in hot and confined environments.